Temporal changes in trauma according to alcohol sale restrictions during the South African national COVID-19 lockdown - Daniel J. van Hoving (Elsevier, 2021)
Introduction: The South African government enforced various alcohol sale restrictions during the COVID-19 lockdown in order to reduce hospital admissions related to alcohol-associated injuries. A cross-sectional study was performed to describe the temporal changes in trauma according to alcohol sale restrictions during the South African national COVID-19 lockdown. Methods: Data from all trauma-related patients presenting to the emergency centre of Mitchells Plain Hospital from 01/03/2020 till 29/9/2020 and corresponding periods during 2019 were exported from an existing database. The relationship between variables was determined with the χ2-test, Fisher's exact test, independent samples median test or t-test. A sub-analysis compared similar 2020 lockdown levels when a second alcohol ban were instituted while most business were allowed to operate (level 3b – alcohol banned versus level 3 – alcohol restricted). Results: Total number of trauma presentations were 539 (14.6%) less in 2020 (n = 3160) than in 2019 (n = 3699); the mean number decreased by 2.5 per day (95% CI −2.9 to −2.1). Lockdown levels with an alcohol ban had on average 4.8 less patients per day than corresponding periods in 2019 (p < 0.001). No significant difference was observed in lockdown levels with alcohol sale restrictions (mean difference per day −0.4, p = 0.195). Trauma presentations increased significantly (mean difference per day 7.0 (95% CI 6.5 to 7.5)) from 2020 lockdown levels with alcohol sales ban (mean per day 11.4) to 2020 lockdown levels with alcohol sale restrictions (mean per day 18.4). Significantly less patients (mean −3.2 (95% CI −3.9 to −2.5)) presented during 2020 lockdown level 3b (alcohol sales banned, mean 13.9) compared to level 3 (alcohol sales restricted, mean 17.1). Conclusion: Temporal changes in trauma were observed according to alcohol sale restrictions during South Africa's COVID-19 lockdown periods. Significantly less trauma cases presented during periods with an alcohol ban compared to periods where alcohol sales were only restricted.